Assessment, Intervention, and Language Development Monitoring Model for Children with Speech Delay - Rivo Panji Yudha; Yufi Fisalma; Priyanti, Nita; Siahaan, Leroy Holman (Journal of Scientific Research, Education, and Technology (JSRET), 2025)
This study aims to develop a Model for Assessment, Intervention, and Monitoring of Language Development for Children with Speech Delay (MAP-ASD) in West Jakarta. The high prevalence of speech delay (23.3%) and the lack of context-appropriate assessment instruments (87.5% of PAUDs do not have specific instruments) are the basis for the urgency of this research. Using the 4D model development approach (Define, Design, Develop, Disseminate), the study involved 15 children with speech delay and 15 PAUD teachers. Validation was carried out by three experts in the fields of child developmental psychology, learning assessment, and speech therapy. The results showed that the MAP-ASD has very good validity (CVI 0.97), high reliability (Kappa 0.77; ICC 0.81), and very good practicality (T-Score 67.7). Effectiveness testing demonstrated significant improvements in children's language skills following MAP-ASD-based intervention, with an average increase of 5 points (22.7%), highest in semantics (6 points) and lowest in syntax and pragmatics (4 points). Mild speech delay cases demonstrated the best response (26.9% improvement), while severe cases continued to show significant progress (20.0%). This model integrates a multilingual approach tailored to the West Jakarta context and links assessments with specific intervention recommendations. MAP-ASD significantly contributes to filling the gap in contextual assessment tools for speech delay in Indonesia, enabling early identification and appropriate interventions that improve the quality of inclusive education at the early childhood education (ECE) level